ANALISIS FAKTOR-FAKTOR PENEMPATAN KARYAWAN TERHADAP KEPUASAN KERJA KARYAWAN DI PT YUNIKO ASIA PRIMA DI KOTA BANDUNG - Agustriyana, Darwis (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The research objective is to be achieved (1) To know how the placement of employees and job satisfaction in a textile factory Yuniko Asia Prima (2) To determine the effect of the placement of employees on the level of job satisfaction in a textile factory Yuniko Asia Prima. The study populations were employees at a textile factory Yuniko Asia Prima and the sample is taken as many as 83 employees by the simple technique of sampling with multiple regression analysis. The results showed that the placement of employees at PT Asia Prima Yuniko already well underway. Employees of the company were placed in accordance with academic achievement as well as its experience, and in accordance with the physical and mental health. Also according to the employees, the company delivers wages in accordance with the number of dependents received, and promotion according to the marital status of an employee owned. Employee satisfaction gets a positive response from employees. It can be seen that the needs of the wages, the work itself, promotion, co-workers and supervisors and supervisor monitoring can fulfill the wishes of employees. Influence simultaneously, variable placement of employees has a significant influence with employee job satisfaction, and the results of the analysis of the coefficient of determination, the variable placement of employees by 69% has an influence on the formation of employee satisfaction. However partially, variable marital status and age did not have influence on job satisfaction of employees at PT Yuniko Asia Prima. Keywords: staffing, employee satisfaction.